Еколого-ценотична характеристика проектованої пам’ятки природи «Городецьке городище» - Першко, Я. А.; Хом’як, І. В. (НУБіП України, 2025)
Abstract The designed natural monument of local importance "Gorodetske hillfort" is located in a picturesque corner of Zhytomyr region near the village of Gorodets. The settlements belong to 10 classes, 13 orders, 17 unions and 22 associations. The spring has socio-economic significance as a recreational and sacred object. Many local legends and beliefs, as well as religious rituals, are associated with it.
Ecological and cenotic characteristics of the designed natural monument "Gorodetske hillfort"
Keywords: культурна спадщина; водні артерії; екологія; cultural heritage; water arteries; ecology